(untitled) (Journal of Hama University, 2026)
Introduction: Rheumatoid arthritis is an autoimmune disease that affects more women than men, and mainly affects the elderly. The World Health Organization (WHO) reported in 2019 that 18 million people worldwide are affected by rheumatoid arthritis. About 70% of people with rheumatoid arthritis are women, and 55% of them are older than 55 years. Encouraging patients to adopt appropriate and sound self-care behaviors is an important factor contributing to the successful management of the disease. Aim:Evaluation of self-efficacy and factors affecting self-care practices among patients with rheumatoid arthritis. Research materials and methods: A descriptive study was conducted on an available sample of 200 patients diagnosed with rheumatoid arthritis of both sexes who visited the joints department and clinics in Lattakia University Hospital, Jableh National Hospital, and Lattakia National Hospital. Data were collected by individual interviews using a questionnaire tool, then the data were transcribed and analyzed using SPSS. Results: The results showed that most of the sample members had a good level of self-efficacy, and that the highest percentage of them had an average level of self-care practices. Recommendations: Conduct educational seminars and educational programs for patients about self-care practices, develop a self-care program for rheumatism patients.